The Jewels in English Language Teaching: Attributes of Quality English Language Teachers in Second Language Setting. - Ag-Ahmad, Norazrina; Syed Mohamed, Ahmad Thamrini Fadzlin; Bakar, Erda Wati (Pertanika Journal of Social Sciences & Humanities, 2024)
The growing demand for high-quality English language teachers who can effectively facilitate language learning has prompted the need for research in this area. By utilising a phenomenological approach and in-depth interviews, this study explores the lived experiences of ten experienced English language teachers from the Eastern part of Malaysia and five stakeholders in the English language teaching (ELT) field. The aim is to gain insights into their perceptions of what constitutes a quality English language teacher. The findings highlight that passion for teaching, cognitive abilities, social-emotional competencies, personality traits and a concept of 'going beyond teaching' are crucial for quality teachers. This research contributes to a deeper understanding of essential attributes that define a quality English language teacher, enabling teacher training institutions to refocus their curriculum and incorporate courses that prepare teachers holistically and enhance second language teaching and learning, particularly in the social-emotional domain. Several recommendations for including specific components in teacher training programs are also discussed.